Moral Development and Ethical Decision Making in Tax Compliance: Evidence from Accountants in Malaysia - A. D. Tejwant Singh, Veerinderjeet Singh (1999)
The objective of this study is to identify and empirically investigate some factors that may influence ethical decision-making by accountants in a tax compliance conflict situation. This study attempts to determine whether moral development influences tax compliance decision-making and behaviour in the context of Kohlbergs' cognitive moral development theory. It also specifically considers the individual and joint effects of a number of variables such as moral development, individual differences (type of firm and legitimacy) and size of tax deduction (contextual variable). An empirical model was developed from a review of the literature on ethical decision-making in business and marketing. The model considers the individual and joint influences of the variables stated above. Accountants' ethical decision-making was operationalised in terms of the response to three tax compliance conflict situations. Eleven null hypotheses were developed for testing. A representative sample of one hundred and eighty accountants from Certified Public Accounting (CPA) firms were selected as subjects for the mail survey. The data was analysed using multiple regression as well as probit and logit estimation techniques. Of the eleven null hypotheses, one was rejected whereas there were mixed results for five others. The results for these five hypotheses were significant (at the 1% level) in two out of the three conflict situations. The contextual variable was a significant explanatory variable. Moral development was only significant when it interacted with either the contextual variable, the type of firm or legitimacy in different conflict situations. Although moral development was not a significant explanatory variable, it did perform well as an interaction variable. As such, the results lend support to the interactionist model used in the study. The type of firm variable performed well with regard to one of the conflict situations, thus indicating that there are differences in the way respondents from different firms make decisions. As for socio-economic variables, the most significant variable was membership of a professional body. The overall conclusion that emerges from this study is that moral development is important as an interaction variable when it interacts with other variables such as context, type of firm or legitimacy. Various recommendations are made following the findings of the study. These involve educational interventions, ethics intervention, the role of professional bodies and improving legitimacy. Future research is also suggested in respect of further testing of the model used in the study.